Peran Pendidik Dalam Pengembangan Efektivitas Evaluasi Hasil Belajar Peserta Didik - Afifah, Firyal Nabila (CV. ITTC INDONESIA, 2023)
Student learning outcomes are an important aspect that will be used to make decisions regarding the planning and implementation of future learning. In order to know student learning outcomes, evaluation is needed. A good evaluation depends on the planners and implementers, namely educators. Educators must be able to rack their brains to find appropriate and effective evaluation instruments with students. The aim of this research is to clarify and describe the important role of educators in developing the effectiveness of evaluating learning outcomes. The data collection method used is literature study from journals that have been accredited by Sinta, data processing uses qualitative descriptive methods. The research results show that educators must be able to plan, implement and report evaluations of student learning outcomes.